STATUS ENTOMOLOGI VEKTOR DEMAM BERDARAH DENGUE DI KELURAHAN PERKAMIL KECAMATAN TIKALA KOTA MANADO TAHUN 2011 - Joy Victor Imanuel Sambuaga (POLTEKKES KEMENKES MANADO, 2011)
This study aims to determine how much the state entomologist in this case the density of vectors of dengue (Aedes sp. larvae) Perkamil In the village of Manado City. This type of research is observational (survey). Data were collected in January 2011 by using a single method in each larva 15 houses located at the site of dengue fever cases in Perkamil Village in 2010. Each location in the buffer DBD with a radius of 100 meters from the homes of cases and selected 15 homes to be sampled.Implementation of the survey using the larval form of detention entomology equipment, pipettes, flashlight and GPS. From each sample point coordinates taken home and then checked kebrdaan larvae in each container that contains water inside and outside the home. On each container that was found larval tail of larvae taken by detention or using a pipette using mouth if the container is small, after the larvae entered into the bottle labeledand check the type of species by using light microscopy. Research shows the magnitude of House Index (HI) 48.61%, larva-free rate (ABJ) 51.39), Container Index (CI) 23.33% and Breteau Index (BI) 107.8. From the number of positive containers larvae, bath / WC is the type most often found in larvae of container from 29.64%.